The Influence of Individual Characteristics, Technology Use, Environmental, Social, and Governance (ESG) Practices on Financial Performance of Village Credit Institutions (LPD) in Abiansemal District - Ni Made Diah Juniari; I Ketut Puja Wirya Sanjaya; I Gusti Ngurah Sanjaya (Journal of Governance, Taxation and Auditing, 2026)
This study aims to analyze the influence of individual characteristics, technology utilization, and Environmental, Social, and Governance (ESG) practices on the financial performance of Village Credit Institutions (Lembaga Perkreditan Desa/LPD) in Abiansemal District, Badung Regency, Bali Province. The research was conducted on all LPDs operating in Abiansemal District, with the object of study being the financial performance of LPDs as influenced by the three variables. The research population consisted of 34 active LPDs spread across 34 traditional villages. The sampling technique used was purposive sampling with specific criteria; therefore, each LPD was represented by three respondents, namely the chairperson, treasurer, and financial or accounting staff. Accordingly, the total sample size in this study was 102 respondents. Data were collected through questionnaires and analyzed using multiple linear regression analysis to examine the effect of each independent variable on financial performance. The results indicate that individual characteristics, technology utilization, and ESG practices have a significant influence on the financial performance of LPDs in Abiansemal District. These findings highlight the importance of human resource quality, the use of information technology, and the consistent implementation of ESG principles in supporting improved financial performance and the sustainability of LPDs. This study is expected to provide practical contributions for LPD management and serve as a reference for future research by incorporating additional variables and expanding the research scope.